2012
DOI: 10.4303/jem/q120503
|View full text |Cite
|
Sign up to set email alerts
|

Immune Characterization of Wild-CaughtRattus norvegicusSuggests Diversity of Immune Activity in Biome-Normal Environments

Abstract: Biome depletion, or loss of co-evolved constituents within the ecosystem of the human body, has become the leading suspect in epidemics of allergic, inflammatory and autoimmune diseases associated with post-industrial culture. Immunity in wild and laboratory rats has been used as a model for immunity in biomenormal and biome depleted environments, respectively. In this study, the ranges of numerous immune parameters (such as cytokine production and cell surface marker expression) in 8 wild rats overlapped with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In other words, no one particular helminth was necessary: the rules for reconstitution are apparently flexible. Consistent with this view, data from the analysis of immunity in wild rodents [ 47 , 48 ] indicate that the ‘normal’ immune system, one free of the influences of modern medicine and water treatment technology, is highly variable depending on the environment. Thus, ‘normal’ immunity probably covers a very wide range, again suggesting that the rules for biome reconstitution are quite flexible.…”
Section: Biome Reconstitution To Compensate For Evolutionary Mismatchmentioning
confidence: 89%
See 1 more Smart Citation
“…In other words, no one particular helminth was necessary: the rules for reconstitution are apparently flexible. Consistent with this view, data from the analysis of immunity in wild rodents [ 47 , 48 ] indicate that the ‘normal’ immune system, one free of the influences of modern medicine and water treatment technology, is highly variable depending on the environment. Thus, ‘normal’ immunity probably covers a very wide range, again suggesting that the rules for biome reconstitution are quite flexible.…”
Section: Biome Reconstitution To Compensate For Evolutionary Mismatchmentioning
confidence: 89%
“…(ii) Helminths are known to produce a wide range of molecules that tune down the immune system, thus decreasing the propensity for allergic and autoimmune disease [45]. (iii) Studies of both human [46] and rodent [47, 48, 49, 50] immune systems in individuals with a normal (not modified by modern technology and medicine) biome show an immune system with profoundly different regulation and a hyporesponsive posture compared with immune systems from biome-depleted individuals. Evolutionary biology: Mammalian coevolution with helminths and other species (e.g. protozoans) have resulted in ‘adjustments’ in our immune function [43] so that effective immune function is dependent on the presence of a normal biome (see text).…”
Section: Evolutionary Mismatch As the Underlying Cause Of Pandemics Omentioning
confidence: 99%
“…Fewer eosinophils (as a percent of total granulocytes) (Lin et al 2012a) and lack of eosinophils (Mirkov et al 2018) in peripheral blood of wild compared to laboratory rats might be an indication of their increased turnover, as a decline of these granulocytes has been noted during inflammatory response to infection in laboratory mice (Bass 1975;Ohnmacht et al 2007). However, high white blood cell counts with a shift in favor of neutrophils and high relative numbers of monocytes were noted in more than 20% of wild rats (Kataranovski et al 2009), as well as greater representation of peripheral blood monocytes (as a fraction of total peripheral blood leukocytes) (Lin et al 2012a), which is an indication of a systemic inflammatory response established as a response to the need for newly produced cells in these individuals (Schwartz & Weiss 1991;Asimakopoulos 1999). Lower surface expression of L-selectin/CD62L and increased expression of MHC class II and CD81 on peripheral blood T cells from wild compared to laboratory rats (Trama et al 2012) reflect their activation state.…”
Section: Peripheral Blood Leukocyte Immune Activitymentioning
confidence: 99%
“…Differences in the levels of other pro-inflammatory cytokines (e.g. chemokines and TNF) in the sera of wild compared to laboratory rats (Lin et al 2012a;Trama et al 2012) as well as great variation observed for some circulating cytokines in wild rats could be ascribed to differences in environmental influences, exposure to infectious agents in the first place.…”
Section: Systemic Cytokine Responsesmentioning
confidence: 99%
“…While some mice are capable of reducing infection quickly, others can respond by immunological means less swiftly and/ or with the lower intensity. The use of another approach that promoted analysis of vast numbers of aspects of immune activity on small numbers of wild rats (fewer than 10) (Lin et al 2012;Trama et al 2012) added further data to the list of immune activity parameters which differ from those in laboratory rats, although their importance in the immunity of wild-caught individuals might not be determined. However, small numbers of both wild-caught and laboratory rats which were analyzed (n = 8, each) may not mirror the state of immunity in the general population of wild rats.…”
Section: Introductionmentioning
confidence: 99%